The Use of Interactive Media as an Innovation in History Education in Secondary Schools: A Systematic Literature Review - Pahmi Kurniawan; Suhendro; Nabila Septiana; Syarifuddin; Rani Oktapiani (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2026)
advances in digital technology have driven changes in the history learning process in secondary schools through the use of technology-based interactive media. History education, which previously tended to be conducted in a conventional manner, is now undergoing innovation through the use of digital multimedia, interactive videos, educational apps, virtual museums, and web-based educational platforms. This study aims to analyze the use of interactive media as an innovation in history learning in secondary schools and to identify its impact on students’ learning motivation, learning outcomes, interest in learning, critical thinking skills, and participation. The study employed a Systematic Literature Review (SLR) method, utilizing data collection techniques through a search of scholarly articles on Google Scholar, Garuda, DOAJ, and ResearchGate. The analyzed articles were published between 2020 and 2026, with a final total of 15 articles meeting the study’s inclusion criteria. The results of the study indicate that the use of interactive media has a positive impact on history learning because it enhances student engagement, strengthens understanding of the material, and fosters a more active and communicative learning environment. Furthermore, interactive media is considered more effective than conventional learning because the learning process is more visual, engaging, and contextual. The findings of this study indicate that the development of interactive media plays a crucial role in supporting innovative history education that meets the needs of 21st-century education.